First record: Dendroidichnites (D. irregulare) in Late Triassic marginal lacustrine deposits of the Passaic Formation, west-central New Jersey. Issue 4 (2nd October 2021) - Metz, Robert
ABSTRACT: Fine-grained siltstones of the Late Triassic Passaic Formation, near Milford, New Jersey have yielded the first evidence of the trace fossil Dendroidichnites irregulare in the Newark Supergroup of New Jersey. Associated trace fossils include Helminthoidichnites, Scoyenia, Spongeliomorpha, and the reptile footprint Rhynchosauroides, representing the Scoyenia Ichnofacies. Associated sedimentary structures include desiccation cracks, raindrop impressions, cross-bedding, and tool marks. The Passaic sediments were deposited under shallow water lacustrine shoreline conditions subject to periodic subaerial exposure.